Praksa, habitus in polje - Stanković, Peter (Teorija in praksa, 1999)
Sociological theory of Pierre Bourdieu represents not only an amalgam of interesting and often even proving insights, but also one of the most important attempts for thoeretical synthesis in contemporary sociology. As many other sociologists, Bourdieu also tries to overcome simplifyed and one-sided classical theories, which focused exclusively on social structures, or on human agency. In order to overcome this futile cleveage on two opposed meta-theoretical traditions, Bourdieu introduces a dynamic triad praxis-habitus-field. He hopes that this solution will alow to understand bothsides of social dynamics in their intertwined essence. The article analyses the three notions and shows how Bourdieu has not achieved his goal: his solution adequatly conceptualizes only the structural side of social reality (the field), while the other side, human agency (or praxis), remains basically only a dependent variable.
Keywords: Bourdieu, Pierre; sociološke teorije; družbena struktura; družbeni razredi; družbeno delovanje; teorija družbe